Big Data Analytics and Online Promotional Strategies to Boost Digital Business Sales: Analisis Big Data dan Strategi Promosi Online untuk Meningkatkan Penjualan Bisnis Digital - Nurhaeni, Tuti; Azka, Refa; Arasid, Nova Syahrani; Sunengsih, Meriyana; Evans, Richard (ADI Bisnis Digital Interdisiplin Jurnal, 2025)
In todays competitive and dynamic digital business landscape, the utilization of Big Data Analytics (BDA) and online promotional strategies has become a critical factor in driving sales growth and sustaining competitive advantage. This study aims to analyze how the integration of BDA with digital promotional strategies can enhance the effectiveness of marketing campaigns and support more strategic decision-making in online business management. Employing a mixed-methods approach, the research combines quantitative data from a survey of 120 digital business managers and qualitative insights from in-depth interviews with decision-makers in the e-commerce and startup sectors. The findings reveal that the implementation of BDA enables companies to identify consumer trends, personalize promotions in real time, and optimize marketing budget allocation. Data-driven promotional strategies have proven to be more adaptive and directly impact the improvement of conversion rates and customer loyalty. However, challenges such as the complexity of data system integration, short-ages in analytical talent, and concerns over consumer privacy present significant barriers that require strategic management. This study underscores that synergy between analytical capabilities and measurable digital promotion is essential to achieving sustainable sales growth in the digital era. The results offer practical contributions for industry practitioners and academics in designing marketing approaches that are data-driven and outcome-oriented. By highlighting both the opportunities and obstacles in integrating BDA with digital marketing strategies, this research emphasizes the need for aligning technological advancement with organizational readiness and strategic focus to fully leverage the benefits of big data in modern business operations.